2014
DOI: 10.1111/nph.12827
|View full text |Cite
|
Sign up to set email alerts
|

Fungal nutrient allocation in common mycorrhizal networks is regulated by the carbon source strength of individual host plants

Abstract: SummaryCommon mycorrhizal networks (CMNs) of arbuscular mycorrhizal (AM) fungi in the soil simultaneously provide multiple host plants with nutrients, but the mechanisms by which the nutrient transport to individual host plants within one CMN is controlled are unknown.Using radioactive and stable isotopes, we followed the transport of phosphorus (P) and nitrogen (N) in the CMNs of two fungal species to plants that differed in their carbon (C) source strength, and correlated the transport to the expression of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
195
5
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 251 publications
(212 citation statements)
references
References 58 publications
11
195
5
1
Order By: Relevance
“…Some studies have demonstrated that the carbon supply of the host acts as an important trigger for P and N transport in the AM symbiosis [10,12,75]. However, there are also other reports in which the carbon to nutrient resource exchange was not directly correlated [13].…”
Section: Role Of Carbon In Fungal P and N Transportmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have demonstrated that the carbon supply of the host acts as an important trigger for P and N transport in the AM symbiosis [10,12,75]. However, there are also other reports in which the carbon to nutrient resource exchange was not directly correlated [13].…”
Section: Role Of Carbon In Fungal P and N Transportmentioning
confidence: 99%
“…Recent results demonstrated that both P and N are important determinants for the AM symbiosis and that the colonization of the plant host is controlled by feedback mechanisms between both nutrients [12]. For example, both, P and N starvation of the plant induce a nutrient stress transcriptome that is favorable for AM colonization.…”
Section: Contribution Of the Arbuscular Mycorrhizal Symbiosis To Planmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally accepted that some plants and AMF are able to reduce resource transfer to symbiotic partners, when not receiving a "satisfying" benefit in return. 13,14 In the -1 a) was used as the reference transcript. Mycorrhizal acquisition of inorganic phosphate of sorghum was estimated based on uptake of labeled phosphorus only available for AM fungi.…”
Section: Introductionmentioning
confidence: 99%